MANAJEMEN LAYANAN BK DALAM MENDUKUNG KESEJAHTERAAN PSIKOLOGIS PESERTA DIDIK SISWA DAN SISWI KELAS 3 DI REJANG LEBONG TAHUN 2025 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT The study was based on the importance of managing Guidance and Counseling (GC) services that support students' well-being. To analyze the impact of GC service management on third-year Nursing students 'psychological well-being at the 3 IDHATA, five kinds of research methods were used, including a quantitative and descriptive correlational approach that employs 36 respondents chosen from the base of purposive sampling. Questionnaires were adjusted in a Likert-scale format and average was taken according to tion standard deviation significantly, Data were analyzed with descriptive statistics, and normality tests were conducted followed for check the linear relationships of samples through simple regression methods. GC management was rated high, with students 'psychological well-being in the middle. Regression analysis indicated that GC management had a significant influence on psychological well-being, with an R Square value of 0375. This analysis concludes that GC’s effective service management significantly improves students’ psychological well-being and must be further strengthened with closer planning and supervision. Keywords: GC Management, Psychological Well-Being, School Counseling.